Centella asiatica ameliorates AlCl3 and D-galactose induced nephrotoxicity in rats via modulation of oxidative stress - Vishnumukkala, Thirupathirao; Gopalakrishna, Prarthana Kalerammana; Karikalan, Barani; Thomas, Warren; Jagadeesan, Saravanan; Musa Chiroma, Samaila; Mohd Nor, Nurul Huda; Mohd Moklas, Mohamad Aris (Biomedical Informatics, 2024)
Nephrotoxicity is a condition caused by toxic effects of medications and poisons resulting in the rapid decline of kidney function. Centella asiatica is a medicinal herb with antioxidative and anti-inflammatory characteristics that is used to treat a variety of ailments. The present study intends to explore the ability of Centella asiatica in preventing AlCl3 and D-Galactose-induced nephrotoxicity in rats. In this study 30 male albino Wistar rats were induced with nephrotoxicity using AlCl3 and D-galactose, and oral administration of Centella asiatica extract (100, 200, and 300mg/kg/day) was administered for 70 days. The kidneys were extracted after treatment and levels of oxidative and antioxidative enzymes, serum creatinine, and serum albumin were measured. The kidney's histopathological changes were studied. Administration of Centella asiatica extract significantly increased serum albumin, superoxide dismutase (SOD), and catalase levels in kidney homogenates while suppressing serum creatinine and malondialdehyde (MDA) levels and attenuating histopathological changes associated with nephrotoxicity. Centella asiatica extract lowered serum creatinine and oxidative stress levels in a drug-induced nephrotoxicity rat model, while simultaneously increasing serum albumin levels, as evidenced by mitigation of histological changes and normalisation of biomarkers of oxidative stress in the kidney.